Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 5: 1738 - Juni 1739 - Gottsched, Johann Christoph (Briefwechsel, 2011)
In the years 1738/39, Gottsched was mostly concerned with two events: his departure from the "Deutsche Gesellschaft" which he had been heading and the resulting developments, and the continuation of his disputes on the philosophy of Christian Wolff which he had been conducting with the Lutheran-Orthodox theologians. Through the support of the influential Imperial Count Ernst von Manteuffel, Gottsched now acquired strong political backing. This is documented by 52 of the total of 204 letters published in this volume, a correspondence in which Mrs Gottsched also soon became involved. The letters of other correspondents also deal with Wolff's rationalist philosophy, as well as other very varied themes such as theater, teaching of the German language in schools, the problems of Leipzig students, newspaper polemics, planned translation projects and the competing editions of the writings of Martin Opitz, the "father of German poetry", that were undertaken in Leipzig and Zurich.